Pemanfaatan Tanaman Minyak Atsiri Sebagai Pengendali Hama Tikus Padi (Biopestisida) Di Kabupaten Sukabumi - Lela Lailatul Khumaisah; Lela Mukmilah Yuningsih; Asep Kadarohman (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
The chemical content in essential oils have activities on microbes, biopesticides, pathogenic vector insects in humans and animals, including Mentha arvensis and Mentha piperita (mint plants) which have antifertility and antibacterial effects, Vetiveria zizanoides (vetiver root) as insects repellent, Cymbopogon nardus (lemongrass) has an activity against plant pathogenic bacteria and antifungals, and Rosmarinus officinalis (rosemary) has locomotor activity of mice and antibacterial. Essential oils are effective against target organisms, compatible, safe and non-toxic, so they have enormous potential to be developed as biopesticides in controlling rice pests. On the other hand, pests and diseases are problems that always disturb rice farmers, including in Sukaresmi and Kebon Pedes villages, Sukabumi. Therefore, the use of essential oil plants has been carried out to control rice mouse pests. This has been started from the preparation of seeds to process of planting the four types of essential oils (mint, lemongrass, and rosemary) in the fields as intercrops and the procurement of essential oil distillation sets. Based on observations, the growth and development of essential oil plants as intercropping plants on rice runs normally and its impact on rice pests, especially in mice, is quite significant with not found rats around the planting area. Keywords: Mint, lemongrass, rosemary, essential oil, biopesticide